Effectiveness of thidiazuron and naphthaleneacetic acid during adventitious shoot bud induction and plant regeneration from leaf explants of rhinacanthus Nasutus (l.) Kurz - R.ELANGOMATHAVAN,; S.HARIHARAN,; P.KALAIVANAN,; S.NANCY BEAULAH, (International Journal of Pharma and Bio Sciences, 2017)
An efficient adventitious shoot bud induction and regeneration protocol from leaf explants was established for Rhinacanthus nasutus within a short period 35-40 days. Leaf explants were cultured on Murashige and Skoog (MS) medium was supplemented with 30 g/l sucrose and different concentrations of cytokinin and auxin viz., Thidiazouron (TDZ) (1.0 – 5.0 mg/l), 6- Benzylaminopurine (BAP) (0.5 – 5.0 mg/l) , Kinetin (Kn) (0.5 – 5.0 mg/l), and Combination of Napthelene acetic acid (NAA) 0.5 - 2.0 mg/l. The maximum number of adventitious shoot buds (42.0) per explants observed at Thidiazouron (TDZ) 1.0 mg/l and Naphthalene acetic acid (NAA) 0.5 mg/l. The maximum number of rootlets (11.0) and length (4.2 cm) response were obtained with IBA (0.5 mg/l). The highest adventitious shoot bud proliferation efficiency (42 adventitious shoot buds per explant) was obtained in the present study through primary callus on the primordial region. The influence of TDZ and NAA culture medium had a major role effect on adventitious shoot bud induction and consequent plant regeneration. Optimum adventitious shoot bud induction (95 %) was achieved on MS medium supplemented with TDZ (1.0 mg/l) and NAA (0.5 mg/l). This protocol resulted here for R. nasutus is an efficient method and reproducible could be used for agrobacterium-mediated genetic transformation experiments.